2000
DOI: 10.1029/1999jb900423
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved study of charge generation and propagation in igneous rocks

Abstract: Abstract. Electrical resistivity changes, ground potentials, electromagnetic (EM), and luminous signals preceding or accompanying earthquakes have been reported many times, in addition to ground uplift and tilt and other parameters. However, no concept exists that would tie these diverse phenomena together into a physically coherent model. Using low-to medium-velocity impacts to measure electrical signals with microsecond time resolution, it is observed that when gabbro and diorite cores are impacted at relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 84 publications
1
144
0
4
Order By: Relevance
“…However, this paper shows that the greatest chances of observing the decrease anomalies of the foF2 and TEC occur on the 4th days before the M ≥ 5.0 earthquakes under study. Although possible causal mechanisms are not fully understood (Bolt 1999;Freund 2000;Kim and Hegai 1999), we found that the lead time of anomalies to the M ≥ 6.0 earthquakes tends to be shorter than that to the M ≥ 5.0 earthquakes. Figure 3a depicts variations of the foF2 to be more fluctuated than those of the TEC.…”
Section: Results and Interpretationsmentioning
confidence: 79%
“…However, this paper shows that the greatest chances of observing the decrease anomalies of the foF2 and TEC occur on the 4th days before the M ≥ 5.0 earthquakes under study. Although possible causal mechanisms are not fully understood (Bolt 1999;Freund 2000;Kim and Hegai 1999), we found that the lead time of anomalies to the M ≥ 6.0 earthquakes tends to be shorter than that to the M ≥ 5.0 earthquakes. Figure 3a depicts variations of the foF2 to be more fluctuated than those of the TEC.…”
Section: Results and Interpretationsmentioning
confidence: 79%
“…Such a structure might provide a key to a possible solution to pre-seismic ionospheric anomalies. Recently, several mechanisms for lithosphere-atmosphere-ionosphere coupling, such as the atmospheric electric field, the atmospheric gravity wave (AGW), and gas emanation, have been proposed (Pulinets and Boyarchuk, 2004;Freund, 2000;Molchanov et al, 2006). If positive holes excited around the epicenter diffuse and outflow from the epicenter, an upward electric field is generated on the surface of the earth (Freund, 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has also been proposed that positively charged holes, associated with microfracturing prior to earthquakes, diffuse from the focal zone to the ground surface. There are laboratory experiments that sup port this possibility [Freund, 2000]. How ever, such preseismic electric fields on the ground followed by preseismic ionospheric anomalies have not yet been observed.…”
Section: Proposed Mechanismsmentioning
confidence: 99%